Life histories of two hyperbenthic mysids (Mysidacea: Mysidae) in an open estuary. Issue 3 (3rd July 2021) - Bierschenk, Beate M.; Burns, Carolyn W.; Schallenberg, Marc; Closs, Gerard P.
ABSTRACT: Mysidae are widely distributed in aquatic ecosystems and form a large proportion of the hyperbenthic biomass in estuaries. The seasonality, spatial distribution and reproductive biology of the two hyperbenthic mysid species, Tenagomysis chiltoni and Tenagomysis novaezealandiae, were studied in an open estuary. Sampling was conducted bi-monthly at night between February 2008 and April 2009. These two mysid species are spatially segregated along a salinity gradient, with T. chiltoni upstream and T. novaezealandiae downstream in the estuary. The life cycle and breeding dynamics of T. chiltoni (bivoltine life cycle) and T. novaezealandiae (multivoltine life cycle) were similar to those described in intermittently closed estuaries, but their breeding period (December to April) was relatively shorter and densities were lower. Life-stage specific segregation in summer in both mysid species likely provided favourable conditions for maximum growth rates, short maturation times, and sheltering, enhancing reproductive success of both mysid species.